Characterization of a bioactive Jagged1-coated polycaprolactone-based membrane for guided tissue regeneration. (April 2018) - Nowwarote, Nunthawan; Chanjavanakul, Phunphimp; Kongdecha, Pattanit; Clayhan, Panipuk; Chumprasert, Sujin; Manokawinchoke, Jeeranan; Egusa, Hiroshi; Pavasant, Prasit; Osathanon, Thanaphum
Highlights: PCL/HA exhibited more hydrophilicity and surface roughness than PCL. PCL and PCL/HA supported hPDLs cell attachment and growth. Jagged1 immobilized PCL/HA upregulated HES1 expression and enhanced ALP activity in hPDLs. Abstract: Objective: The aim of the present study was to develop a Jagged1-coated polycaprolactone (PCL) membrane and to evaluate the response of human periodontal ligament cells (hPDL) on this membrane in vitro. Methods: Membranes were prepared from PCL and PCL-incorporated hydroxyapatite (PCL/HA). The membranes' surface roughness, surface wettability, and mechanical properties were examined. An indirect affinity immobilization technique was used to coat the membranes with Jagged1. Membrane cytotoxicity was evaluated using LIVE/DEAD and MTT assays. The morphology of the cells on the membranes was observed using scanning electron microscopy. hPDL alkaline phosphatase (ALP) enzymatic activity and mineral deposition were examined using an ALP assay and Alizarin Red S staining, respectively. Notch target gene mRNA expression was determined using real-time polymerase chain reaction. Results: The PCL/HA membranes exhibited a significantly reduced surface contact angle, decreased maximum tensile strain, and ultimate tensile stress. However, the surface roughness parameters were significantly increased. The PCL and PCL/HA membranes were not cytotoxic to hPDL in vitro . hPDLs attached and spread on both membrane types. Further, indirect affinity immobilized Jagged1 on the membranes upregulated hPDL Notch target gene expression. After culturing in osteogenic medium, Jagged1-immobilized PCL/HA membranes significantly enhanced hPDL ALP enzymatic activity. Conclusion: Indirect immobilized Jagged1 PCL/HA membranes could be further developed as an alternative guided tissue regeneration membrane to promote osteogenic differentiation in periodontal defects.